2013
DOI: 10.1158/0008-5472.can-12-4453
|View full text |Cite
|
Sign up to set email alerts
|

Pak1 Kinase Links ErbB2 to β-Catenin in Transformation of Breast Epithelial Cells

Abstract: p21-activated kinase-1 (Pak1) is frequently upregulated in human breast cancer and is required for transformation of mammary epithelial cells by ErbB2. Here we show that loss of Pak1, but not the closely related Pak2, leads to diminished expression of β-catenin and its target genes. In MMTV-ErbB2 transgenic mice, loss of Pak1 prolonged survival, and mammary tissues of such mice showed loss of β-catenin. Expression of a β-catenin mutant bearing a phospho-mimetic mutation at Ser 675, a specific Pak1 phosphorylat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 45 publications
2
72
0
Order By: Relevance
“…In contrast to these findings, previous studies showed that deletion of either Pak1 or Pak3 is tolerated, and mice lacking either of these genes do not display significant vascular defects (12). These results are consistent with the fact that Pak2 is the main isoform expressed in ECs (35) and the idea that Pak1 and Pak2 have distinct and often opposing roles in mediating various cellular events, as has been suggested by a number of recent studies (36)(37)(38).…”
Section: Discussionsupporting
confidence: 84%
“…In contrast to these findings, previous studies showed that deletion of either Pak1 or Pak3 is tolerated, and mice lacking either of these genes do not display significant vascular defects (12). These results are consistent with the fact that Pak2 is the main isoform expressed in ECs (35) and the idea that Pak1 and Pak2 have distinct and often opposing roles in mediating various cellular events, as has been suggested by a number of recent studies (36)(37)(38).…”
Section: Discussionsupporting
confidence: 84%
“…PAKs are overexpressed or/and hyperactivated in variety of human malignancies including bladder, melanoma, breast, prostate, colorectal, and ovarian carcinoma (13). Importantly, compelling genetic and pharmacologic evidence exists that shows that inhibiting group I PAKs can block transformation by oncogenic drivers such as ERBB2 (14), and K-RAS (15). Thus, this kinase is a well-validated anti-cancer target.…”
Section: Introductionmentioning
confidence: 99%
“…Pak1-deleted tumors had reduced ERK1/2 and Akt activation and expressed less ␤-catenin. Additionally, treatment of subcutaneous BT474 cell xenografts with the Pak1 inhibitor PF-3758309 completely blocked tumor growth, whereas the ␤-catenin-TCF4 inhibitor iCRT14 was without effect (90). The Cdc42 regulated kinase Pak4, which signals distinctly from Paks 1-3, may also play a role in mammary gland tumorigenesis.…”
Section: Rho Effectors In Mammary Gland Tumorigenesis and Metastasismentioning
confidence: 98%
“…Expression of the Pak1 autoinhibitory domain in MDA-MB-631 cells, which blocks activation of Paks 1-3, reduced subcutaneous tumor growth and inhibited ERK and Akt activation in SCID mice (89). Moreover, Pak1 deletion significantly delayed tumorigenesis in MMTV-Neu mice (90). Pak1-deleted tumors had reduced ERK1/2 and Akt activation and expressed less ␤-catenin.…”
Section: Rho Effectors In Mammary Gland Tumorigenesis and Metastasismentioning
confidence: 99%